2001
DOI: 10.1210/jcem.86.11.8010
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk for Nonmedullary Thyroid Cancer in the First Degree Relatives of Prevalent Cases of Nonmedullary Thyroid Cancer: A Hospital-Based Study

Abstract: The genetic basis for nonmedullary forms of thyroid cancer (NMTC) is less well established than that of medullary thyroid cancer. However, epidemiological and family studies suggest that a proportion of NMTC may be due to inherited predisposition. To estimate the familial risk of thyroid cancer, we conducted a hospital-based case-control study at the Princess Margaret Hospital in Toronto, Ontario, Canada, and at 2 university hospitals in Montréal, Québec, Canada. We obtained pedigrees from 339 unselected patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(34 citation statements)
references
References 30 publications
1
30
1
2
Order By: Relevance
“…NMTC represents more than 95% of all thyroid cancer, and four histologic subtypes can be distinguished: papillary (85%), follicular (11%), Hürthle syndromes such as Cowden disease (multiple hamartoma syndrome), familial adenomatous polyposis, or Carney complex (8). The reported prevalence of FNMTC varies from 2.5 to 11.3% of all NMTC patients (5,9,10,11). Given the high prevalence of thyroid cancer in the general population, the occurrence of FNMTC may not be rare.…”
Section: Introductionmentioning
confidence: 99%
“…NMTC represents more than 95% of all thyroid cancer, and four histologic subtypes can be distinguished: papillary (85%), follicular (11%), Hürthle syndromes such as Cowden disease (multiple hamartoma syndrome), familial adenomatous polyposis, or Carney complex (8). The reported prevalence of FNMTC varies from 2.5 to 11.3% of all NMTC patients (5,9,10,11). Given the high prevalence of thyroid cancer in the general population, the occurrence of FNMTC may not be rare.…”
Section: Introductionmentioning
confidence: 99%
“…Previous population studies have shown that the risk of thyroid cancer is increased fivefold to ninefold in individuals with a first‐degree relative with thyroid cancer . When there are two affected family members with thyroid cancer, the probability that the affected members have a familial syndrome is reported to be 31–53% .…”
Section: Introductionmentioning
confidence: 99%
“…The most common type of thyroid cancer is papillary thyroid cancer, which comprises 80% of all thyroid tumors . Approximately 5% of cases of papillary thyroid cancer are familial . Epidemiologic data suggests that inherited factors contribute to papillary thyroid cancer .…”
mentioning
confidence: 99%